Análisis del sistema de control de prácticas de conducción de la Escuela Aneta de la ciudad de Babahoyo - Coello Barreto, Katherine Tatiana (2020)
The present case study aims to carry out an analysis of the control system of driving practices of the ANETA school in the city of Babahoyo, To identify the causes of the problems that said systems currently present, the qualitative research paradigm was used for this. the same that allowed us through an analysis to determine the characteristics of the driving practice control system of the ANETA school in the city of Babahoyo, and thus suggest solutions to the problems encountered, the type of bibliographic research that helped us to the scientific foundation of the variables of the research topic was also used.